ANALISIS CAMPURAN SERAT PELEPAH TANGKAI PISANG KEPOK DENGAN RESIN KATALIS TERHADAP KEKUATAN TARIK - Rahbini Rahbini; Heryanto Budiono Soemardi; Sarjiyana Sarjiyana (Jurnal Teknologi Terapan, 2017)
The strength of material is a parameter to show mechanical material characteristic, which is determined based on the endurance of supporting external force. In materials science, it is know as the various meanings of strength based on how far external force causes the impact on the material. Resin material is a polymer produced by chemical industry and is used in various applications, among other are packing, textile (example: rope, thermal clothing, and carpet), while banana stalk which contain water has not been used in engineering. The mixture of banana stalk fiber with catalyst resin is called composite. Composite is a solid material produced by the combination between two or more diffrent materials to obtain better characteristic which cannot be obtained from every component.Testing method of composite is done by being pressed with long , thick, wide size based on the standard. The up and down part of the material is clamped and then the testing instrument pulls the tested object so that can show maximum pulling power of 10.2 x 105 kg/m2 with a speed of 100 mm/minute.